HOTS based project in mechanical engineering department - pertiwi, dewanti ratna ((JELE) Journal Of English Language and Education, 2019)
In this 21st century education, preparing learners to have high order thinking skills (HOTS) is important to make them ready face the global era. HOTS (analyze, evaluate, create) is the continuous phases of LOTS (remember, understand, apply).Â  HOTS in a project based instruction is proposed to be able to promote the skills needed in the 4.0 era (critical thinking, communication, creativity, and collaboration). This research focused on a HOTS-based project in a mechanical engineering, Adisutjipto College of Technology. Based on the observation in the previous semester, the students needed to improve their HOTS that the research applied an action research study. The projects were allocated in two course objectives; identifying the tools in mechanical engineering and identifying the components of an airplane. They were chosen due to the supported authentic materials exist in the college workshop laboratory, hangar, and airplane museum near the college. The results were the learners enjoyed the learning and improved the engagement in a group work, the critical thinking in finding fruitful information, the creativity in creating presentation, and the speaking skill in presenting in front of other people.